Determination of Mothers level of Knowledge toward Children’s Developmental Milestones visiting Dr. Jamal Ahmed Rashid Pediatric Teaching Hospital in Sulaimaniyah City / Iraq - Majeed, Bahar Nasradeen (Journal of Neonatal Surgery, 2025)
Background: Recognizing child developmental milestones is essential for the early detection of developmental delays and promoting optimal growth in children. While studies in developed countries emphasize the beneficial effects of maternal awareness on child development, such research is scarce in the Arab region. This study aimed to assess the level of knowledge among mothers concerning their children's developmental milestones in Sulaimaniyah city, Iraq, and to investigate the relationship between this understanding and their socio-demographic factors. Methods: A quantitative and descriptive research approach was employed from December 15th 2022 to March 15th 2023 at Dr. Jamal Ahmed Rashid Pediatric Teaching Hospital in Sulaimaniyah city. A purposive sample of 160 mothers with children under the age of two was selected. Data were gathered through a structured questionnaire including socio-demographic attributes and knowledge on developmental milestones. The reliability of the questionnaire was strong (Cronbach's alpha = 0.831). Descriptive statistics and chi-square tests were conducted for data analysis using SPSS version 24. Results: The findings indicated that highest number of mothers had fair level of overall understanding regarding child developmental milestones. Statistical examination showed significant differences between maternal age and awareness of motor and language development; between financial condition and knowledge of motor development; and between child's birth order and understanding of motor, cognitive, and language development (p≤0.05). Significant associations were found between maternal education with language development level showed a significant correlation with knowledge of language development and number of children with language and cognitive development. Conclusions and recommendations: more than half of mothers have fair level of knowledge in overall areas of developmental millstones. Statistically, there are associations between mother’s age and child’s birth orders with mother’s level of knowledge in term of motor, cognitive, and language domains. Recommendation: Enhance the mother's level of knowledge and awareness about child developmental milestones through implementing comprehensive educational programs about this important issue is highly recommended.